Educational role of art history as a school subject area in programmes of formal education in Slovenia: the aspect of vzgoja, according to general European guidelines - Dolšina, Marjana (Journal of Education Culture and Society, 2020)
Programmes of formal education establish a systematic transfer of knowledge as well as universal values from one generation to another. By that, they ensure the survival of social structures, prevent radical disruptions in their continuity, and serve as basis for general development of a society. Their content and didactic arrangements include interweaving of two basic aspects: the cognitive one and the one related to vzgoja (i.e. upbringing, moral/value education etc.). The latter aims to achieve the ideals of a tolerant, just and lifelong learning society, but seems to be facing increasing challenges, mainly emerging from neoliberal capitalist mentality. Art history as a school subject area in elementary and secondary education may provide an insight beneath the surface of historical events. Thus, it helps develop a critical view towards them and consequently towards the present real-life situations, which contributes to ascending the taxonomic scale of conative educational goals.